Shallow and Undoped Germanium Quantum Wells: A Playground for Spin and Hybrid Quantum Technology. (23rd January 2019) - Sammak, Amir; Sabbagh, Diego; Hendrickx, Nico W.; Lodari, Mario; Paquelet Wuetz, Brian; Tosato, Alberto; Yeoh, LaReine; Bollani, Monica; Virgilio, Michele; Schubert, Markus Andreas; Zaumseil, Peter; Capellini, Giovanni; et al.
Abstract: Buried‐channel semiconductor heterostructures are an archetype material platform for the fabrication of gated semiconductor quantum devices. Sharp confinement potential is obtained by positioning the channel near the surface; however, nearby surface states degrade the electrical properties of the starting material. Here, a 2D hole gas of high mobility (5 × 10 5 cm 2 V −1 s −1 ) is demonstrated in a very shallow strained germanium (Ge) channel, which is located only 22 nm below the surface. The top‐gate of a dopant‐less field effect transistor controls the channel carrier density confined in an undoped Ge/SiGe heterostructure with reduced background contamination, sharp interfaces, and high uniformity. The high mobility leads to mean free paths ≈ 6 µm, setting new benchmarks for holes in shallow field effect transistors. The high mobility, along with a percolation density of 1.2 × 10 11 cm −2, light effective mass (0.09 m e ), and high effective g ‐factor (up to 9.2) highlight the potential of undoped Ge/SiGe as a low‐disorder material platform for hybrid quantum technologies. Abstract : A two‐dimensional hole gas is demonstrated in a strained and shallow germanium quantum well, located 22 nm below the surface. The buried and undoped channel is populated via top‐gating. The high mobility of half a million cm 2 V −1 s −1, light effective mass (0.09 m e ), and high effective g ‐factor (9.2) highlight the potential of germanium for spin and hybrid quantum technologies.